Who loses income during the COVID-19 outbreak? Evidence from China. (August 2020) - Qian, Yue; Fan, Wen
Abstract: The COVID-19 pandemic has transformed every facet of society. In addition to directly affecting population health, the economic impact of this social shock has begun to be palpable at the individual level. Situated in this context, this research note draws on data collected from Mainland China in March–April, 2020 to examine the individual-level economic toll of the COVID-19 outbreak. We investigate how individuals' income (when surveyed) has changed relative to before the outbreak, and pay particular attention to the potentially unequal distribution of economic vulnerability based on structural (dis)advantages and COVID-19 related conditions. We show that education, family economic status, Communist Party membership, state-sector employment, and urban hukou—all long-standing status markers in China—mitigate the adverse effects of the COVID-19 outbreak on individuals' income losses. In addition, people who live in families or regions that were hit harder by COVID-19 are more likely to experience income losses. Taken together, this study shows that the COVID-19 pandemic not only exacerbates pre-existing social inequalities but also creates new forms of disparities. Therefore, instead of acting as a great equalizer, the pandemic may well magnify the social distribution of economic vulnerability. To alleviate inequality and aid post-pandemic recovery, public policies need to be oriented toward vulnerable and marginalized populations.